Ovarian reserve testing in the prediction of recurrent pregnancy loss - Kükrer, Sadik; Arlıer, Sefa; Karaman, Seyfettin (Journal of Surgery and Medicine, 2020)
Aim: Approximately 1-2% of reproductive women have faced recurrent pregnancy loss (RPL). Ovarian reserve testing in the prediction of recurrent pregnancy loss is not usually performed. In this study, we aim to evaluate whether there were any differences between patients with and without a history of recurrent pregnancy loss (RPL) with regards to anti-Mullerian hormone (AMH), follicle stimulating hormone (FSH), luteinizing hormone (Lh), estradiol (E2) levels and basal follicle count. Methods: This case-control study was conducted between 1 January 2013 and 1 January 2015 in the Gynecology and Obstetrics Clinic of Adana Numune Training and Research Hospital. A total of 370 patients aged 17-37 years with a diagnosis of RPL during that 2-year period were contacted by telephone. Further evaluation was made of 40 patients who met the study criteria and gave verbal consent. Patients were called to the Gynecology Polyclinic for assessment on the 3rd day of their menstrual cycle, and a control group was formed of 40 patients with similar demographic characteristics who were referred to the Gynecology Polyclinic and met the study criteria. Results: The mean basal follicle count was determined as 9.4 (2.7) in the study group and 8.9 (2.5) in the control group (P=0.092). The mean AMH values in the RPL and control groups were 3.50 (1.92) ng/mL and 3.66 (2.14) ng/mL, respectively (P=0.718). The mean FSH values in the RPL and control groups were 6.77 (1.87) mIU/mL and 7.01 (1.90) mIU/mL, respectively (P=0.494). Mean LH values were measured as 5.6 (1.8) mIU/mL in the study group and 4.9 (1.7) mIU/mL in the control group. Mean E2 values were 87.7 (83.9) pg/mL and 48.4 (27.9) pg/mL in the study and control groups, respectively. Conclusion: While no difference was found between the RPL and control groups in respect of AMH and FSH values in the ovarian reserve tests, the basal follicle count of the patients with recurrent pregnancy loss was found lower than that of the control group.